Phase diagram of polymer blends in confined geometry - Müller, Marcus (2001)
Within self-consistent field theory we study the phase behavior of a symmetrical binary AB polymer blend confined into a thin film. The film surfaces interact with the monomers via short range potentials. One surface attracts the A component and the corresponding smei-infinite system exhibits a first order wetting transition. The surface interaction of the opposite surface is varied as to study the crossover from capillary condensation for symmetric surfaces fields to the interface localization/delocalization transition for antisymmetric surface fields. In the former case the phase diagram has a single critical point close to the bulk critical point. In the latter case the phase diagram exhibits two critical points which correspond to the prewetting critical points of the semi-infinite system. Only below a triple point there is a single two phase coexistence region. The crossover between these qualitatively different limiting behaviors occurs gradually, however, the critical temperature and the critical composition exhibit a non-monotonic dependence on the surface field. The dependence of the phase behavior for antisymmetric boundaries is studied as a function of the film thickness and the strength of the surface interactions. Upon reducing the film thickness or decreasing the strength of the surface interactions we can change the order of the interface localization/delocalization transition from first to second. The role of fluctuations is explored via Monte Carlo simulations of a coarse grained lattice model. Close to the (prewetting) critical points we observe 2D Ising critical behavior. At lower temperatures capillary waves of the AB interface lead to a pronounced dependence of the effective interface potential on the lateral system size.